1998
DOI: 10.1097/00007632-199806010-00019
|View full text |Cite
|
Sign up to set email alerts
|

The Bagby and Kuslich Method of Lumbar Interbody Fusion

Abstract: Carefully selected middle-aged patients with chronic low back pain secondary to degenerative disc disease can be treated effectively and safely by skilled surgeons using the Bagby and Kuslich device for one- and two-level interbody fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 455 publications
(64 citation statements)
references
References 47 publications
4
58
1
1
Order By: Relevance
“…The fusion rate in the ALIF group cannot be conclusively proven. Anterior interbody fusion rates vary between 19% and 96%, depending on the method of evaluation, fixation technique, and graft material [4,13,15,18,20,22,26,28,30,33,38,42,47,51]. However, radiological trabecular continuity is difficult to see with the titanium implant, making it difficult to assess how many patients with a satisfactory clinical outcome do not have a bony fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion rate in the ALIF group cannot be conclusively proven. Anterior interbody fusion rates vary between 19% and 96%, depending on the method of evaluation, fixation technique, and graft material [4,13,15,18,20,22,26,28,30,33,38,42,47,51]. However, radiological trabecular continuity is difficult to see with the titanium implant, making it difficult to assess how many patients with a satisfactory clinical outcome do not have a bony fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Vamvanij et al [54] reported an 88% fusion and a 63% success rate with the Bagby and Kuslich (BAK) cage and posterior facet fusion. Kuslich et al [28] reported a 91% fusion rate, 84% pain relief and 91% functional improvement at 24 months' follow-up using the BAK method of lumbar interbody fusion. Other authors [1,2,3,10,16,50,52] have reported more than 70% satisfactory clinical results with instrumented interbody fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Stender et al reported good results in 76% of their patients with a cobalt-chrome molybdenum implant for anterior fusion; however, the subjectively reported results for return to work and pain reduction showed good results in only 68% [17]. The Bagby and Kuslich method [8] has a fusion rate of 98% when used in an anterior approach and 100% when used in a posterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…The worst clinical results were obtained for multisegmental implantation, with fusion rates of 71% [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cages were implanted initially stand-alone in combination with bone grafts [2], with generally satisfying clinical success [24] and high fusion rate, generally over 90% (reviewed in [3]). Although device failures were not reported, interbody cages may subside into the vertebral bodies (14% subsidence rate in a literature study [7]), thus loosing the intervertebral height restoration achieved postoperatively [35].…”
Section: Introductionmentioning
confidence: 99%